Implementasi Kebijakan Pelayanan Publik Pengoperasian KMC Kartini 1 Rute Semarang - Karimunjawa PP Oleh Dinas Perhubungan Provinsi Jawa Tengah Tahun 2014 – 2016 - Agung Prasetya; Muhammad Adnan (Journal of Politic and Government Studies, 2018)
KMC Kartini 1 as an implementation of public service policy needs to be seen how the process of implementation of its policy, whether in the end will get a result in accordance with the goal or target of the policy itself. Judging from the above reasons why research on this implementation is done 1) In terms of management or operation KMC Kartini 1 where less effective and efficient. 2) The objective in terms of increasing PAD is considered not to reach the target. 3) There is a competition of ships The research method used is qualitative approach with data collection technique that is observation, interview and document. Informants or resource persons in this research are Kasi Operational and Staff of Central Java Transportation Office of Transportation, KMC Kartini 1 Customer Service, KMC Kartini 1 Captain. The result of research shows that KMC Kartini 1 public service policy reach 3 out of 4 main objectives. First, provide the means of sea transportation Jepara-Karimunjawa. Secondly, increasing tourism in Jepara regency. Third, to encourage economic growth in Jepara regency. As for the fourth, increasing revenue is considered less successful. The failure occurs due to several factors. First, from the relationship of cooperation management. Second, the condition of the old ship. Third, the competition of the ship. Fourth, weather conditions. to strive for the achievement of the failed objective the Department of Transportation of Central Java Province did two things: first, transfer the management to SPJT where it is rejected by SPJT. Secondly, the KMC Kartini 1 vessel chartering effort to the private sector failed to be implemented. Recommendations for Central Java Provincial Government KMC Kartini should not be managed by government agencies in this case the Department of Transportation of Central Java Province. Second, if the management is still charged to the Department of Transportation, the Department of Transportation of  Central Java Province can make a breakthrough cooperation with the private sector. Third, the condition of the ship, especially parts of machinery that are older than 5 years should be replaced with a new engine or even a new ship. Keywords : Implementation of Policy, Public Service